1984
DOI: 10.1073/pnas.81.19.6207
|View full text |Cite
|
Sign up to set email alerts
|

Human T-cell leukemia virus (HTLV-I) transcripts in fresh and cultured cells of patients with adult T-cell leukemia.

Abstract: We examined the DNA and RNA of fresh leukemic cells (five patients) and long-term cultured T lymphocytes (four patients) from patients with adult T-cell leukemia for the presence of human T-cell leukemia virus (HTLV-I) sequences. In all cases HTLV-I previrus was found and several species of viral mRNAs were observed in all cell lines. We used HTLV DNA probes representing the gag, pol, and env genes and pX regions and the U3-and US-specific sequences to characterize the genetic content of the viral transcripts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(84 citation statements)
references
References 31 publications
7
76
0
1
Order By: Relevance
“…Hence, upregulation of HTLV-1 expression has been linked to T cell activation events mediated via PKC expression. However, despite the constitutive expression of IL-2R (Depper et al, 1984;Popovic et al, 1983;Yodoi et al, 1983) and in some cases the production of IL-2 (Depper et al, 1984;Gootenberg et al, 1981;Hattori et al, 1981) by circulating HTLV-1-infected T lymphocytes in vivo, HTLV-1 gene products are expressed at low levels (Franchini et al, 1984;Hoshino et al, 1983;Sugamura et al, 1984). Viral regulatory protein transcripts have been detected using reverse transcriptase PCR in lymphocytes of HTLV-1-infected patients, but expression is low and occurs in only a small number of cells (Gessain et al, 1991; 0001-2241 © 1994 SGM Kinoshita et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, upregulation of HTLV-1 expression has been linked to T cell activation events mediated via PKC expression. However, despite the constitutive expression of IL-2R (Depper et al, 1984;Popovic et al, 1983;Yodoi et al, 1983) and in some cases the production of IL-2 (Depper et al, 1984;Gootenberg et al, 1981;Hattori et al, 1981) by circulating HTLV-1-infected T lymphocytes in vivo, HTLV-1 gene products are expressed at low levels (Franchini et al, 1984;Hoshino et al, 1983;Sugamura et al, 1984). Viral regulatory protein transcripts have been detected using reverse transcriptase PCR in lymphocytes of HTLV-1-infected patients, but expression is low and occurs in only a small number of cells (Gessain et al, 1991; 0001-2241 © 1994 SGM Kinoshita et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The tax gene can also transform NIH 3T3 and Rat-i fibroblasts (6). Previous studies have failed to readily detect HTLV-I antigens (7)(8)(9) and mRNA (10)(11)(12) in the leukemic cells of ATL patients, suggesting that HTLV-I gene expression is not required for the progression to and maintenance of the leukemic state and that the role of the virus may be limited to the induction of polyclonal T-lymphocyte proliferation years to decades before the development of ATL. This proliferation could lead to secondary events, increasing the chance for leukemia, at which stage HTLV-I gene expression would not be necessary (13).…”
mentioning
confidence: 99%
“…This could ex plain the predominance of chronically activated Tax-specific CTLs in these individuals (see Section 4.2.2). ln HTLV-I-Infected PBMCs, the level of Tax mRNA expression per infected cell is the same in asymptomatic carriers and in TSP/HAM patients, but 10w or absent in uncu1tured A TLL samples (Franchini et aL., 1984;Furukawa et aL., 1995).…”
Section: Proviralload and Clonai Integration Of Htlv-i Infectionmentioning
confidence: 98%
“…Early experiments suggested that A TLL cells in vivo a1so do not express HTL V -1 mRN As (Franchini et al, 1984). Whi1e sorne expression of viral mRN A in fresh A TLL samples has been seen using RT-PCR (Berneman et al,1 992a; Koralnik et al, 1992b), It is unclear whether this occurred in A TLL cells or other HTL V -1 infected T-cells.…”
Section: Duferences Between Htlv-j-tran~fonned T-cells and Atll Cellsmentioning
confidence: 99%